Learning Design of Citizenship Education in Indonesia After Ahok Tragedy, a Shape of Social Media and Critical-Literacy in Educational Process - Husniyatus Salamah Zainiyanti; Atmari Atmari (Tarbiyatuna: Jurnal Pendidikan Islam, 2018)
From the fist decade when Soekarno declared Indonesia as Pancasila State, until 71th independence nowaday. Educationally, Indonesia had not an ideal concept how to indoctrine its form of pluralistic cultures and religions, which were emerged and lived in. Differently from another democratic countries, like USA, Australia, and Europian-Community, which faced the multi-ethnic diaspora, new social movement groups, and imigrant people, they reconcile the new concept of citizenship education system within social and cultural changs, as well as they faced. In facts, citizenship education often deliver as a political education as usual. There are no new approaches and systimatic curricular changes to adopt and adapt what presently heppend in the grassroot-society. So that, this articles will explore some progresive problems that shifted the pluralistic stance of Indonesian People. Eventually, in based on educational system and teaching learning posses in general school. The ultimate aims are growing approaches to teach pure Indonesian citizenship values, seem like, what democratic countries did for their citizen, after political abnormal contestation, such as the rise of radicalism, ethnic or racial conflict, and so on. Thus, this article also will focuss on ‘Ahok Tragedy’ which are re-contested a a living historical conflict; Islamic and Nationalist stance of Indonesian identity.